Prevalence of bacterial vaginosis among reproductive age group women in a tertiary care centre - Nair, Rema V.; Preethi, Raja; Vijayalekshmi, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Vaginal discharge in reproductive age poses a serious problem in the developing countries. Bacterial vaginosis also known as non-specific vaginitis is the most common cause of vaginal infections, detecting the organism at an early stage and initiating a proper treatment is very difficult in our country due to lack of awareness and proper follow-up. The disease manifests in the form of vaginal discharge with or without itching. It has a strong association with preterm labor, preterm premature rupture of membranes and low birth weight in pregnancy. The objective of this study was to find out the prevalence of bacterial vaginosis among the reproductive age group women, in a tertiary care centre. Methods: A cross sectional study was conducted among 150 women of the reproductive age group in the department of obstetrics and gynaecology Sree Mookambika Institute of Medical Sciences over a period of one month October 2018 the diagnosis was made with history and nugents scoring system. Results: Out of the total 150 women enrolled in the study 74 had positive results, 50% of them were of the age group 26-30. Conclusions: The study shows us the high prevalence of bacterial vaginosis.